Importance of fluorine 18 fluorodeoxyglucose (FDG) positron emission tomography (PET)/computed tomography (CT) in detection of post-thyroidectomy recurrence in differentiated thyroid cancer with negative radio-isotope iodine scan, yet, elevated serum thyroglobulin level - Amir Fathy Henfy Younis; Ahmed Farid Yousif; Hamada Mohamed Khater (The Egyptian Journal of Radiology and Nuclear Medicine, 2022)
Abstract Background Thyroid cancer considered the 6th common cancer in female and represents approximately 1% of all cancers. Thyroid cancer is generally characterized by good prognosis, long term survival and low aggressiveness. Its prognosis is related to tumor dimensions, extra capsular extensions, the age at diagnosis and distant metastases sites. Combination between positron emission tomography and computed tomography allow anatomic, functional & molecular information. Aim To demonstrate Fluorine 18 fluorodeoxyglucose positron emission tomography)/computed tomography role for evaluation of post-thyroidectomy recurrence either local or distant metastatic lesions in differentiated cancer thyroid patients with negative radio-isotope iodine scan, yet showing elevated serum thyroglobulin level. Procedure A prospective study included twenty patients with previous history of differentiated thyroid cancer. All patients after history taking and revising the medical sheet underwent Serum Thyroglobulin level & I-131 whole body scan examinations and then Fluorine 18 Fluorodeoxyglucose Positron Emission Tomography/Computed Tomography study. The findings of Positron Emission Tomography/Computed Tomography imaging compared with results of histopathology or follow-up clinical results as a gold standard. Results Fluorine 18 fluorodeoxyglucose positron emission tomography/computed tomography based analysis showed that nineteen true positives and one was true negative as confirmed by the gold standard (Histopathology and clinical follow-up). Thirteen patients had either local recurrence or lymph node metastases without distant metastatic disease, six patients had different distant metastasis. Fluorine 18 fluorodeoxyglucose positron emission tomography/computed tomography based analysis showed that nineteen true positives and one was true negative as confirmed by the gold standard (histopathology and clinical follow-up). The accuracy and sensitivity of Fluorine 18 fluorodeoxyglucose positron emission tomography/computed tomography (95%) were significantly better than those of the Computed Tomography alone (84.2% and 80%, respectively). Conclusions Fluorine 18 Fluorodeoxyglucose positron emission tomography/computed tomography provided a critical role in assessment and management of patients with suspected differentiated thyroid recurrence, presenting with high serum thyroglobulin level and negative radio-isotope iodine scan. It enhances diagnostic accuracy through giving exact anatomical localization of recurrent and/or metastatic tumor foci.